2022
DOI: 10.1136/bmjopen-2022-064104
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing death anxiety among Chinese patients with cancer: a cross-sectional study

Abstract: ObjectiveThe purpose of this study was to investigate death anxiety status among Chinese patients with cancer and identify factors that affect death anxiety.DesignCross-sectional study.SettingChangsha, Hunan Province, China.ParticipantsA total of 286 inpatients diagnosed with cancer were randomly recruited from a tertiary cancer centre and completed the questionnaires between January and June 2021.Primary and secondary outcome measuresThe primary outcome was the status of death anxiety. The secondary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(67 reference statements)
3
6
0
Order By: Relevance
“…Consistent with previous findings (Ding et al, 2015;Gong et al, 2022), we found that education level was negatively correlated with cancer death anxiety. This may be related to the lower education level of patients who are less well informed about their diagnosis and medical procedures and thus show intense fear.…”
Section: Demographicvariablessupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with previous findings (Ding et al, 2015;Gong et al, 2022), we found that education level was negatively correlated with cancer death anxiety. This may be related to the lower education level of patients who are less well informed about their diagnosis and medical procedures and thus show intense fear.…”
Section: Demographicvariablessupporting
confidence: 93%
“…Conversely, higher self-esteem (Yang et al, 2022), spiritual wellbeing (Scheffold et al, 2019), resilience (Gong et al, 2022) and quality of life (Soleimani et al, 2016) are related to lower levels of death anxiety.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the findings of the only existing empirical study are coherent with the hypothesis that fear of death and psychological inflexibility might be positively associated. Gong et al [80], indeed, have recently investigated this subject in patients with cancer, showing a significant positive correlation, with a large magnitude (i.e., > .50), between experiential avoidance and death anxiety. Besides, research has highlighted the interplay between experiential avoidance, anxiety, and fear, showing that individuals who often employ experiential avoidance are more at risk for developing anxiety disorders [68], experience fear of intense emotions, and endorse more frequent worry [81].…”
Section: Discussionmentioning
confidence: 96%